Manta Net: The Golden Method for Sampling Surface Water Microplastics in Aquatic Environments - Pasquier, Gabriel; Doyen, Périne; Kazour, Maria; Dehaut, Alexandre; Diop, Mamadou; Duflos, Guillaume; Amara, Rachid (Frontiers in Environmental Science, 2022)
Microplastics (MPs) (plastic particles <5mm in size) have become the most ubiquitous type of anthropogenic litter contaminating aquatic environments worldwide, and are capable of harming aquatic organisms and entering the food web. Microplastic research has rapidly evolved over several decades, with many studies sampling microplastic in surface waters. For sea surface sampling of MPs, different net devices have been used. But although there is an increasing number of studies using these devices to quantifying MPs in different aquatic environments, data comparison is difficult due to the lack of standardised, harmonised sampling methods and data reporting units. The Manta net device is actually the most commonly used method for sea surface sampling of MPs. The three main parts of this net are: the floating/stabilizing part, the opening mouth and the net bag, and each of them can have its own specifications. These specifications, along with the sampling methods, can be critical for the efficiency of the sampling accurate quantification of MPs in the aquatic environments. The use of different mesh sizes, inconsistency in trawling duration, speed and distance, and in the net opening dimensions, make it impossible to compare the studies between each other. This review analyzes the methodologies and characteristics of Manta nets used for MPs sampling, discussing factors that can impact the efficiency of the sampling and the quantification of MPs, and proposes recommendations in order to improve and standardize the sampling protocol.